2018
DOI: 10.1002/ange.201713003
|View full text |Cite
|
Sign up to set email alerts
|

Densely Packed, Ultra Small SnO Nanoparticles for Enhanced Activity and Selectivity in Electrochemical CO2 Reduction

Abstract: Controlling the selectivity in electrochemical CO 2 reduction is an unsolved challenge.While tin (Sn) has emerged as apromising non-precious catalyst for CO 2 electroreduction, most Sn-based catalysts produce formate as the major product, which is less desirable than CO in terms of separation and further use.T in monoxide (SnO) nanoparticles supported on carbon black were synthesized and assembled and their application in CO 2 reduction was studied. Remarkably high selectivity and partial current densities for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…A detailed performance comparison between this work and other published Sn‐based electrocatalysts for CO 2 reduction to formate is presented in Figure and Table S1 (Supporting Information). [ 10–14,22a,25,30,31 ] The potential window across −0.5 V to −1.5 V with FE formate over 70% obtained from this work is clearly broader than literature studies that typically display “volcano shape” characteristic. Li et al.…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…A detailed performance comparison between this work and other published Sn‐based electrocatalysts for CO 2 reduction to formate is presented in Figure and Table S1 (Supporting Information). [ 10–14,22a,25,30,31 ] The potential window across −0.5 V to −1.5 V with FE formate over 70% obtained from this work is clearly broader than literature studies that typically display “volcano shape” characteristic. Li et al.…”
Section: Resultsmentioning
confidence: 62%
“…To overcome the intrinsically poor electrocatalytic CO 2 reduction performance of a bulk Sn with a large overpotential and low current density, various material engineering strategies have been applied. This includes nanostructuring of Sn to structures such as metallic Sn quantum sheets, [ 10 ] coralline structured SnO x , [ 11 ] SnO 2 porous nanowires, [ 12 ] ultrasmall SnO, [ 13 ] and SnS 2 nanosheets, [ 14 ] that promotes surface area and active sites toward selective formate production. In addition to alloying or doping with metals, such as copper, [ 15 ] silver, [ 16 ] palladium, [ 17 ] nickel, [ 18 ] positive synergetic impact of doping of a nonmetallic element, such as sulfur [ 19 ] or nitrogen [ 20 ] is another attractive approach toward enhancing formate production.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the packing density of functional NPs within a limited electrode volume is challenging in electrodes for energy storage [115][116][117][118] and other integrated nanostructures. [57,[119][120][121] Generally, NP-based electrodes with a high mass density cannot be easily achieved by conventional electrode preparation methods such as doctor blading or electrostatic LbL assembly without additional treatments (e.g., the use of a mechanical press or thermal annealing) due to the low-density nature of polymeric (or carbonaceous) materials and electrostatic repulsive forces among NPs with the same charge. [94,101,[122][123][124] On the other hand, it has been reported that in situ LE-LbL assembly can produce densely packed NP multilayers without any NP agglomeration or segregation because the reported approach does not use charged species and/or bulky polymer ligands in organic media.…”
Section: Ligand Exchange Lbl Assembly For Increased Charge Transfer Omentioning
confidence: 99%
“…However, the formate and acetate production from the CO 2 RR still remains a scientific challenge 22. Major Sn-based catalysts usually suffer from limited reaction selectivity and a narrow range of active voltage,23–25 although a recent Bi-based catalyst has shown high potential for formate generation 26,27. In addition, very few electrocatalysts perform CO 2 reduction to acetate due to the low activity of C–C coupling 28.…”
Section: Introductionmentioning
confidence: 99%